Discussion on Instrument and Equipment Management in Testing Laboratory - Li, Xiang (Journal of Theory and Practice of Social Science, 2023)
The experimental instrument is mainly used for direct detection or auxiliary detection of samples, which is very important to the measurement results of samples. The ultimate purpose of laboratory instrument management is to ensure the effective operation of laboratory management system, strengthen the management level of experimental instruments, improve the ability of experimental instrument management personnel, in the whole laboratory operation process has a decisive role; The laboratory should establish and improve the management process and rules and regulations of experimental instruments to ensure the effectiveness of instruments and provide accurate and reliable test data for customers.